CHALLENGES TO UNIVERSALIZE BASIC SANITATION IN THE RURAL AREA OF BRAZIL - da Conceição dos Santos, Solange Maria; Dantas de Morais, João Silvio; de Arruda, Luciene Vieira (Revista Inclusiones, 2021)
Through a descriptive research, the Brazilian rural basic sanitation scenario is investigated in the following segments: water supply, sewage collection and treatment. Based on the collected data, an analysis was carried out in order to understand the challenges for expanding access to these services. The results found prove the existence of inequality in the provision of these services between regions of Brazil and point to obstacles to be overcome (low service, high investment value and low purchasing power) for universal access in rural areas by the year 2033.